Human Rights and Vulnerability. Examples of Sexism and Ageism - Barranco Avilés, María del Carmen (The Age of Human Rights Journal, 2015)
A human rights based approach applied to the idea of ‘vulnerable group’ connects vulnerability and structural discrimination. The Convention on the Rights of Persons with Disability provides some elements that allow to state that we are facing a new paradigm in the International Human Rights Law. One of the keys for the understanding of this new framework is the assumption of the disadvantage related to vulnerability as, at least in a part, socially built and ideologically justified. Sexism and ageism are examples of how ideologies reinforce vulnerability of women, children and aged persons transforming them in groups which members are in risk of discrimination.